Fabrication of Cellulose Sponge: Effects of Drying Process and Cellulose Nanofiber Deposition on the Physical Strength - Abdul Halim; Yinchao Xu; Toshiharu Enomae (Department of Chemical Engineering, Universitas Gadjah Mada, 2020)
Cellulose sponge was fabricated by regenerating cellulose from a xanthate solution. The solution, which contained sodium phosphate particles as a template to create sponge porosity, was dried at 55, 65, 75 and 85 °C for 2, 4, 6, and 8 h. Mass transfer during the initial and last stages of drying was controlled in terms of temperature and concentration differences, respectively. The activation energy and pre-exponential factor of the mass transfer coefficient were -51,841.947 kJ mol-1 and 7.26×109 m-2 h-1, respectively. Regenerated cellulose contained a crystalline type of cellulose II, and the crystallinity was independent of drying conditions. At a low drying temperature (T≤55 °C) and short drying period (t≤2h), the cellulose was unregenerated. At higher temperatures and longer drying periods, no relationship between temperature and physical strength was observed. Cellulose nanofiber (CNF) was added to the xanthate solution at a ratio of 1:100 of CNF to linter cellulose for xanthation; however, this did not affect the physical strength of the cellulose sponge for both mechanically and chemically fabricated CNF.